Barium titanate-enhanced hexagonal boron nitride inks for printable high-performance dielectrics - Kim,H; Arbab,A; Fenech,Salerno B; Yao,C; MacPherson,R; Kim,JM; Torrisi,F (Nanotechnology, 2022)
Printed electronics have been attracting significant interest for their potential to enable flexible and wearable electronic applications. Together with printable semiconductors, solution processed dielectric inks are key in enabling low-power and high-performance printed electronics. In the quest for suitable dielectrics inks, two-dimensional materials such as hexagonal boron nitride (h-BN) have emerged in the form of printable dielectrics. In this work, we report barium titanate (BaTiO3) nanoparticles as an effective additive for inkjet-printable h-BN inks. The resulting inkjet printed h-BN/BaTiO3 thin films reach a dielectric constant (εr) of ~ 16 by adding 10% of BaTiO3 nanoparticles (in their volume fraction to the exfoliated h-BN flakes) in water-based inks. This result enabled all-inkjet printed flexible capacitors with C ~ 10.39 nF cm-2, paving the way to future low power, printed and flexible electronics.